2010
DOI: 10.1177/1352458510366856
|View full text |Cite
|
Sign up to set email alerts
|

Multiple sclerosis and solar exposure before the age of 15 years: case—control study in Cuba, Martinique and Sicily

Abstract: Few studies report a protective role of childhood solar exposure to multiple sclerosis. Our objective was to confirm the protective role of childhood solar exposure in multiple sclerosis in Cuba, Martinique and Sicily. This was a matched case- control study, and cases met Poser criteria for clinically, laboratory (definite, probable) multiple sclerosis. Controls were resident population, without neurological disorder, living close to cases (within 100 km), matched for sex, age (+/-5 years), residence before ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 38 publications
2
22
0
2
Order By: Relevance
“…Thus, in order to assess whether a postnatal vitamin D supplementation was protective, we devised a new mouse model. In these conditions, the observed EAE clinical course was in accordance with our hypothesis and epidemiological data on sun exposure and dietary vitamin D supplementation in MS [78,79,[81][82][83]. However, before stating that both models (gestational deficiency and post-gestational enrichment) correspond to paradigms of postnatal supplementation, it remains crucial to perform an experiment in which vitamin D-sufficient embryos will be exposed to low levels of vitamin D from birth to weaning.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Thus, in order to assess whether a postnatal vitamin D supplementation was protective, we devised a new mouse model. In these conditions, the observed EAE clinical course was in accordance with our hypothesis and epidemiological data on sun exposure and dietary vitamin D supplementation in MS [78,79,[81][82][83]. However, before stating that both models (gestational deficiency and post-gestational enrichment) correspond to paradigms of postnatal supplementation, it remains crucial to perform an experiment in which vitamin D-sufficient embryos will be exposed to low levels of vitamin D from birth to weaning.…”
Section: Discussionsupporting
confidence: 88%
“…A North American report of 79 pairs of identical twins discordant for MS found that the unaffected twin reported more sun exposure during childhood than did the twin with MS [80]. A case-control study consisting of participants from Cuba, Martinique and Sicily, also observed a consistently reduced risk of MS related to measures of sun exposure before age 15, and increased risk of MS related to sun protection practices before age 15 years of age [81]. Finally, it was found that veterans with relapsing MS who experienced a low sun exposure in the autumn/winter during the ages of 6-15 years had an earlier symptom onset [82,83].…”
Section: Postnatal Influencesmentioning
confidence: 85%
“…This dementia risk factor might be particularly relevant among MENA women because of Burqa that might limit their required natural sun exposure. Sun exposure was earlier shown by the last author to have preventive effect against certain neurological disorders [65]. …”
Section: Discussionmentioning
confidence: 99%
“…In another valuable contribution, they were instrumental in conducting a three-country survey of mutiple sclerosis (MS) that came out with extremely novel findings on the risk and prevention of MS [21]. In particular, outdoor leisure activities, in addition to sun exposure, were for the first time found to be associated with reduced risk of MS, with evidence of a dose-response relationship.…”
Section: Miscellaneousmentioning
confidence: 99%